Development of a Digital-Based Push Up and Sit Up Test Counter - Romi Mardela; Roma Irawan; Anak Agung Ngurah Putra Laksana; Yurmianna Marlina; Ridwan Efendi (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2023)
Based on the needs analysis carried out using the observation need analysis, it was found that the respondents answered with a very high level of need. Therefor this study aimed to develop a test instrument for counting push up and sit up test in one tool that is digitally integrated. The test tool was developed using the Arduino program with an ultrasonic sensor system and displays the counting results of push-up and sit-up test via the LCD. Content validity is used to test the instrument by using professional judment and involving experts in media, sport test and measurement, liguists, and physical conditioning. Then for the small group test of student to push up 110 (boys and girls) and sit up 124 (boys and girls). Data analysis to test the validity of the expert group using percentages, and test the sample group using the product moment correlation formula. The results of the data obtained from the validity test of the tool expert group to measure the ability to push up and sit up were declared feasible. Then, a small group of push-up was stated valid (rcount 0.991 > rtable 0.195) and sit-up also declared valid (rcount 0.866 > rtable 0.147). This study still has weaknesses, especially in the limited number of samples and the quality of movement cannot be controlled through tools, therefore future researchers can increase the number of samples and including other components to assess movement quality.